Full-Day School Impacts in Indonesia: Perspective of Honorary Teachers - - Haiyudi; Sitthipon Art-In (Kelola: Jurnal Manajemen Pendidikan, 2020)
Since Indonesia employed 37.10% teachers that are still in honoraria status/ contracted-status, it is a serious problem. This research used mixed-method to address the goals. Spreading the questionnaire and having in-depth interview are used to get the data. Three experts validated the questionnaires through IOC (Index of Item Objectives Congruence). There are 30 questions that were used to achieve the goals. The reliability of the item is acceptable. The Cronbach value shows .839 which is higher than .70 (.839>.70). The sampling of this rerearch are totally the honorary teachers that are stratified into three groups, young teacher, senior and older teacher based on the working year. However, the result indicates there are significant impacts of FDS implementation to honorary teacher professionally. But the opposite, personal impact of FDS implementation to honorary teachers is not significant. In line with the differences between those three generations that are not so significant